Hubungan antara stail komunikasi dengan kepuasan terhadap ketua - Nor Hafizah, Abd Rahman (2020)
This study discusses the relationship of communication style with the satisfaction of the leader. Focuses on the evaluation of the respondent to the communication style relationship and the satisfaction of the leader. Independent variable in this study are openness, giving support and participation. Quantitative method was used where questionaire was distributed to a total of 120 responden, a total of 80 questionnaires were successfully returned back and anaylse with Statistical Packege Of Social Sciences (SPSS). The results found that there were significant positive relationship between communication style and openness, support, participatory and satisfaction toward the leader. The relationship between giving support and satisfaction to the leader hasteh strongest significant positive relationship than another variable.